Links between type III secretion and extracytoplasmic stress responses in Yersinia - Flores-Kim, Josue; Darwin, Andrew J. (Frontiers in Cellular and Infection Microbiology, 2012)
The cell envelope of pathogenic bacteria is a barrier against host environmental conditions and immunity molecules, as well as the site where many virulence factors are assembled. Extracytoplasmic stress responses (ESRs) have evolved to help maintain its integrity in conditions where it might be compromised. These ESRs also have important links to the production of envelope-associated virulence systems by the bacteria themselves. One such virulence factor is the type III secretion system (T3SS), the first example of which was provided by the pathogenic Yersinia. This article reviews the reported links between four different ESRs and T3SS function in Yersinia. Components of three of these ESRs affect the function and/or regulation of two different T3SSs. The response regulator of the Rcs ESR is involved in positive regulation of the Ysa-Ysp T3SS found in the highly pathogenic 1B biogroup of Y. enterocolitica. Conversely, the response regulator of the Y. pseudotuberculosis Cpx ESR can downregulate production of the Ysc-Yop T3SS, and at least one other envelope virulence factor (invasin), by direct repression. Also in Y. pseudotuberculosis, there is some evidence suggesting that an intact RpoE ESR might be important for normal Yop production and secretion. Besides these regulatory links between ESRs and T3SSs, perhaps the most striking connection between T3SS function and an ESR is that between the Psp (phage shock protein) and Ysc-Yop systems of Y. enterocolitica. The Psp response does not affect the regulation or function of the Ysc-Yop system. Instead, Ysc-Yop T3SS production induces the Psp system, which then mitigates T3SS-induced envelope stress. Consequently, the Y. enterocolitica Psp system is essential when the Ysc-Yop T3SS is produced.